Fabrication and characterization of ferrocenece containing hydrogel for glucose biosensor application - Crulhas, Bruno R. [UNESP]; Ramos, Naira P. [UNESP]; Basso, Caroline R. [UNESP]; Costa, Vladimir E. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Esg, 2014)
A detailed electrochemical study of a novel microsystem biosensor based on ferrocene (Fc) intercalated poly(ethylene) glycol (PEG) and its potential use in the development of amperometric biosensors is presented. A redox hydrogel electrode, fabricated by covering the PEG-FC on the surface of gold microelectrode, exhibits a quasi reversible electrochemical characteristic. The characterization and dependence of Fc concentration to construct the biosensor were carried out by cyclic voltammetry measurements. The sensitivity, repeatability and linearity of the new glucose biosensor are found to be excellent over earlier reported glucose biosensor.
Keywords: Biosensor; glucose detection; redox mediator